Dynamic Tokenization for Next-Gen Payment Security: A Self-Evolving Approach - Uday Pioneer Kola, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores dynamic tokenization as a transformative security approach in digital payment systems. Starting with evaluating traditional static tokenization's inherent vulnerabilities, the article establishes how these limitations have enabled sophisticated cyber attacks, resulting in substantial financial losses globally. It then introduces dynamic tokenization as a paradigm shift that creates continuously evolving tokens based on contextual factors, demonstrating enhanced protection against modern threats. The article further analyzes how integrating dynamic tokenization with blockchain technology establishes a decentralized security framework with immutable transaction records and programmable security logic through smart contracts. Additionally, the article examines the synergistic combination of FIDO2 standards and biometric authentication with dynamic tokenization to address the human element in security. Real-world implementations across digital wallets, contactless payments, open banking initiatives, and cross-border transactions provide compelling evidence of dynamic tokenization's effectiveness in revolutionizing payment security while improving operational efficiency and user experience.
Keywords: Dynamic tokenization; blockchain integration; biometric authentication; cybersecurity; payment fraud prevention